The feasibility of one-stage flexible ureteroscopy lithotripsy in solitary kidney patients with 1–3 cm renal stones and risk factors of renal function changes. Issue 1 (1st January 2021) - Pan, Yang; Chen, Han; Chen, Hualin; Jin, Xiaoxiang; Zhu, Yunxiao; Chen, Gang
Abstract: Purpose: To compare perioperative outcomes and long-term renal function changes between prior stenting (PS) and not prior stenting (NPS) before flexible ureteroscopy lithotripsy (f-URS) for solitary kidney patients. Methods: Solitary kidney patients with 10–30 mm renal stones were enrolled in this historical control study. Perioperative parameters and complications were compared. Stone-free was defined as the absence of any residual stones on a CT scan. Renal function changes were evaluated by estimated glomerular filtration rate (eGFR) and adjusted for body surface area. A decrease in the eGFR over 20% was identified as 'deterioration' in renal function. The follow-up period was at least 6 months. Logistic regression was used to identify risk factors of renal function deterioration. Results: Of the 76 patients included, 40 cases experienced prior stenting before f-URS. The average stone diameter was 16.8 ± 4.7 mm, ranging from 10.0 to 28.4 mm. Initial SFR was 85.0 and 83.3% in the PS and NPS groups, respectively ( p = 0.842), while SFR after the second procedure was 97.5 and 94.4% ( p = 0.926). Seven PS and 5 NPS patients developed complications ( p = 0.666). At the postoperative 6 months, seven patients showed a deteriorated renal function. Surgical time in minutes was identified as a risk factor for renal function deterioration after the operation (OR = 1.061, 95% CI: 1.015–1.109, p = 0.009, per minute). Conclusion: It appears that one-stage f-URS without PS could be feasible for 10–30 mm renal stones in solitary kidney patients, and less surgical time might be beneficial to protect renal function.